Subcutaneous dirofilariasis due to Dirofilaria immitis in a dog in Brazil: first report - Welitânia Inácia da Silva; Alexander Rodrigo Dantas Gomes; Maria Carolina de Francisco; Janete Madalena da Silva; Hodias Sousa de Oliveira Filho; Thais Ferreira Feitosa; Vinícius Longo Ribeiro Vilela (Revista Brasileira de Parasitologia Veterinária, 2023)
Abstract The aim of this study was to report on the presence of microfilariae of Dirofilaria immitis causing nodular pyogranulomatous dermatitis in a dog in the state of Rio Grande do Norte, northeastern Brazil. A 4-year-old male dachshund dog with lesions in the nostrils and left dorsolateral regions was treated. Tests were requested to aid in making the diagnosis, such as skin cytology, Knott's test, thick smear and histopathology of the lesions. From these, presence of a diffuse pyogranulomatous process was observed and, amidst the cellular material, microfilariae of Dirofilaria spp. A conventional polymerase chain reaction test on tissue samples from the lesions revealed the presence of the species D. immitis. Treatment based on ivermectin (3mg) was administered at a single oral dose of 0.6 mg/kg. In the first seven days there was regression of the lesions, but after 30 days there was recurrence. A new treatment was administered, consisting of 10% imidacloprid + 2.5% moxidectin (4-10 mg/kg), with one application per month for 6 months, and doxycycline (100 mg), 10 mg/kg, 1 tablet, 2 times a day, for 30 days. In conclusion, D. immitis microfilariae caused pyogranulomatous lesions in the subcutaneous tissue of a dog. This had not previously been described in Brazil.